Genome-wide Identification and Expression Analysis of Auxin Response Factor Genes in Arabian Jasmine - Xin Huang; Haigang Guo; Lili Yin; Ruigang Wu; Xingwen Zhou (Journal of the American Society for Horticultural Science, 2023)
Auxin response factors (ARFs) are an important family of auxin-mediated proteins that have key roles in various physiological and biochemical processes. To the best of our knowledge, no genome-wide identification of the ARF gene family in Arabian jasmine (Jasminum sambac) has been conducted to date. During this study, 24 ARF genes were identified in the Arabian jasmine genome. A phylogenetic analysis suggested that the 24 Arabian jasmine ARFs (JsARFs) were clustered into seven groups and distributed on 11 of the 13 Arabian jasmine chromosomes. The promoter regions of these ARFs were rich in cis-responsive elements related to hormone responses, light responses, and biotic and abiotic stresses. A collinearity analysis showed that certain genes arose by duplication, such as JsARF6 and JsARF19 and JsARF7 and JsARF24. A subsequent analysis of expression profiles based on RNA sequencing data showed that most genes had differential expression patterns among different tissues. The expression levels of 11 genes under indole-3-acetic acid hormone treatment were determined using quantitative real-time polymerase chain reaction, and the results demonstrated that the expression levels of nine JsARF genes were downregulated. Our findings provide valuable information to create the foundation for further functional investigations of the roles of ARF genes in Arabian jasmine growth and development.